Physical, chemical, sensorial properties and in vitro digestibility of wheat bread enriched with yunnan commercial and wild edible mushrooms. (1st November 2022) - Liu, Yudi; Zhang, Heng; Brennan, Margaret; Brennan, Charles; Qin, Yuyue; Cheng, Guiguang; Liu, Yaping
Abstract: A high glycaemic index diet would cause a rapid increase in blood sugar levels and lead to chronic metabolic disorders. In this study, wheat bread enriched with mushroom ( Pleurotus eryngii and Cantharellus cibarius ) powder at different content (0, 5, 10, and 15 g/100 g replacement based on total weight) was prepared. The effect on the physical, chemical, sensorial, and in vitro digestibility of bread was determined. With the addition of mushroom powder, the total phenolic content of wheat bread significantly ( p  < 0.05) increased. The reducing sugar, hydrogenated index, and expected glycemic index gradually decreased with mushroom powder. The results suggested that mushroom powder could be used as a high-value ingredient to improve the nutritional profile and reduce bread's glycaemic index. Mushroom powder could be used as a natural food ingredient and showed new potential in improving the functional properties of bread products. Highlights: Wheat bread (WB) containing mushrooms powder (MP) exhibited higher quality. The antioxidant properties of wheat bread increased with the MP addition. Adding MP alongside WB retains the ability to reduce carbohydrate digestion in vitro . With the increase of MP addition, WB demonstrated lower expected glycemic index. A d dition of MP promotes health products.